Convergence to fair wage growth? Evidence from European countries on the link between productivity and real compensation growth, 1970–2017 - Theodoropoulou, Sotiria (Brussels, 2019)
"This Working Paper addresses the issue of ‘fair’ wage growth over the last few decades. It assesses whether growth in real compensation is systematically associated with labour productivity growth and, if so, whether the two have ‘decoupled’ in recent years. The paper examines country-specific evidence from 25 Member States and finds evidence for a widening of the wage-productivity gap in the 1970s and 1980s which has only been partially closed in recent years."